Chronic Kidney Disease as a Complication of Cancer. Issue 2 (May 2017) - Selamet, Umut; Abudayyeh, Ala
An exciting era in the diagnosis and treatment of cancer has emerged in the last 2 decades. What was once an often deadly disease has, for many patients, become a chronic disease with longer survival than ever before. However, with the prolongation of life there are further associated complications, such as chronic kidney disease (CKD). This disease has impacts on the patients' treatments, dosage of medications, quality of life, and overall survival. This review illustrates the prevalence of CKD in the cancer patient population and provides an overview of the causes of CKD in these patients. We also explore the bidirectional relationship of cancer and CKD, and elaborate on the cutting edge therapies and their associated renal toxic effects. With a greater appreciation of this important relationship, nephrologists will be better able to work in multidisciplinary teams to improve cancer patients' survival and overall outcomes.